Mózg jako nowy wszechświat – wokół Incepcji Christophera Nolana - Kowalczyk, Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
The article shows the growing interest of science fiction cinema in the human brain and related concepts, such as mind or consciousness. Nowadays, when distant space travel seems unreachable, artists find the exploration potential of the brain very promising. Thus, the main thesis of this analysis says that the brain has become for science fiction cinema the new universe. An excellent example of this paradigm shift is Inception (dir. Christopher Nolan, 2010). In the movie, the mind is depicted as a physical and accessible place, where we can find a lot of mysteries to solve. The characters travel to the deepest parts of subconsciousness because the processes inside the brain are the key to understanding and changing the real world. The article also shows how the director uses the achievements of science fiction cinema and, at the same time, that he postulates a new way of considering the issues relevant to modern neuroscience.